Gestão ambiental na agricultura: um estudo sobre fatores associados à conscientização ambiental em estudantes de uma escola agrotécnica - Chiamenti, ângela Márcia Maronez (2003)
This study deals with environmental issues on agriculture. In this context, the aim of this study is investigate factors able to influence the environmental conscientization of students of a agricultural technicals school about the aspects and environmental impacts related to the agricultural productive process. Besides, the used methodology on this work was to the application of a questionnaire based in Likert-kind scale with closed questions, they are constituted of variables which consisted of groups denominated perception, attitude, communitarian sense, commitment, sel-consciousness, knowledge and student profile. Like data analysis way was used descriptive analysis and chi-square to check the association significance between the perception variable with the variable ones of cited groups. The results obtained show that the environmental knowledge variable was one of the that showed high significance when it associated to the variables of perception group. The students with environmental knowledge showed high consideration that the production activities on agriculture cause large adverse impacts on environment. After the identification of some factors of environmental conscientization are shown recommendations which school must prepare techniques in aware high school of agricultural sciences with the environmental problems which be able to apply sustainable technologies on agriculture instead of traditional ones through the benefit of environment